Animal Models of Chronic Pancreatitis - Makoto Otsuki; Mitsuyoshi Yamamoto; Taizo Yamaguchi (Gastroenterology Research and Practice)
Animal models for CP in rats can be classified into 2 groups: one is noninvasive or nonsurgical models and the other is invasive or surgical models. Pancreatic injury induced by repetitive injections of supramaximal stimulatory dose of caerulein (Cn) or by intraductal infusion of sodium taurocholate (NaTc) recovered within 14 days, whereas that caused by repetitive injection of arginine or by intraductal infusion of oleic acid was persistent. However, the destroyed acinar tissues were replaced by fatty tissues without fibrosis. Transient stasis of pancreatic fluid flow by 0.01% agarose and minimum injury of the pancreatic duct by 0.1% NaTc solution induced progressive pancreatic injury although one alone is insufficient to cause persistent pancreatic injury. However, the damaged tissue was replaced by fatty tissue without fibrosis. Continuous pancreatic ductal hypertension (PDH) caused diffuse interlobular and intralobular fibrosis closely resembling human CP.